Integrating Genome-Wide Association Analysis With Transcriptome Sequencing to Identify Candidate Genes Related to Blooming Time in Prunus mume - Zhang, Man; Yang, Qingqing; Yuan, Xi; Yan, Xiaolan; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2021)
Prunus mume is one of the most important woody perennials for edible and ornamental use. Despite the substantial variation in flowering phenology among P. mume germplasm, the genetic control for flowering time remains to be elucidated. In this study, we examined five blooming-time related traits of 235 P. mume landraces for two years. Based on the phenotypic data, we performed genome-wide association studies combining marker-based and gene-based association tests and identified 1445 candidate genes consistently linked with flowering time across multiple years. Furthermore, we assessed the global transcriptome change of floral bud from two P. mume cultivars exhibiting contrasting bloom dates and detected 617 associated genes that were differentially expressed during flowering process. By integrating the co-expression network analysis, we screened out 191 gene candidates of conserved transcriptional pattern during blooming across cultivars. Finally, we validated the temporal expression profiles of these candidates and highlighted their putative roles in regulating floral bud break and blooming-time in P. mume. Our findings are important to expand the understanding of flowering time control in woody perennials and will boost the molecular breeding for novel varieties in P. mume.